Revision of the genus Pollanisus Walker, 1854(Lepidoptera: Zygaenidae: Procridinae) - Mollet, Bernard; Tarmann, Gerhard M. (Zootaxa, 2023)
The genus Pollanisus is endemic for Australia. Its revision is mainly based on head studies and includes 21 known species and 7 new species, Pollanisus jumbun sp. n., Pollanisus yugambeh sp. n., Pollanisus horakae sp. n., Pollanisus worimi sp. n., Pollanisus kalliesi sp. n., Pollanisus jirrbal sp. n. and Pollanisus nocturna sp. n. Moreover, two species, Pollanisus eumetopus syn. n. and Pollanisus eungellae syn. n., are synonymized with Pollanisus acharon (Fabricius, 1775). The status of 8 unnamed species (Tarmann, 2004) is discussed. New data on the phenology and bionomics are provided. New host plants in the genus Hibbertia (Dilleniaceae) are reported.